Measuring inflation expectations: how the response scale shapes density forecasts - Becker, Christoph; Dürsch, Peter; Eife, Thomas A. (AWI discussion paper series, 2023)
In density forecasts, respondents are asked to assign probabilities to pre-specifted ranges of inflation. We show in two large-scale experiments that responses vary when we modify the response scale. Asking an identical question with modifted response scales induces different answers: Shifting, compressing or expanding the scale leads to shifted, compressed and expanded forecasts. Mean forecast, uncertainty, and disagreement can change by several percentage points. We discuss implications for survey design and how central banks can adjust the response scales during times of high inflation.
Keywords: Graue Literatur